Листи Михайла Грушевського до Олафа Брока (вступна стаття й публікація В.Тельвака) (Український історичний журнал, 2018)
Уперше публікований епістолярій висвітлює малознані контакти українського та норвезького науковців упродовж 1923–1927 рр. Безпосереднім приводом до налагодження листування стала трагедія українського народу – перший за хронологією масовий голод (1921–1923 рр.) на наддніпрянських землях. Знаючи про дружні взаємини О.Брока з Ф.Нансеном, М.Грушевський мав намір спрямувати рятівничу місію останнього в Україну, адже відомою була її суттєва допомога російській інтеліґенції. У цій справі вчений особисто зустрічався з норвезьким славістом у столиці Норвеґії, а також листувався з ним у справах допомоги голодуючим українцям. Під впливом зустрічей зі М.Грушевським і його листів, О.Брок перейнявся трагедією українського народу, організувавши збір коштів. Також у листах М.Грушевського присутнє обговорення й суто наукових проблем. Він інформував О.Брока про діяльність Українського соціологічного інституту, просив позичити потрібні для роботи книги, радився з приводу можливості поширення еміґраційних видань у радянській Україні через місію Ф.Нансена, а в подяку надсилав свої та доньчині праці. Опубліковані листи дозволяють говорити про те, що саме М.Грушевський був ініціатором обрання О.Брока дійсним членом ВУАН у червні 1924 р. В останніх листах міститься обговорення проблеми налагодження співпраці О.Брока з українською Академією наук. The correspondence between Mykhailo Hrushevskyi and Olaf Broch, deposited in the archives of scientists at the Norwegian Library of Manuscript Department in Oslo, are published for the first time. The epistolary illuminates the little-known contacts of scientists during 1923–1927. The immediate cause for the commencement of correspondence was then the tragedy of the Ukrainian people – the first mass famine (1921–1923) on the Dnipro lands. Having known about O.Broch’s friendly relations with F.Nansen, M.Hrushevskyi intended to direct the rescue mission of the latter to Ukraine, as it was famous for its essential assistance to the Russian intelligentsia. Having been driven by this cause, the scientist personally met with the Norwegian Slavist in the capital of Norway, and also corresponded with him in matters of assistance to starving Ukrainians. Under the influence of meetings with M.Hrushevskyi and his letters, O.Broch became involved with the tragedy of the Ukrainian people by organizing a collection of funds. In addition, in the letters to M.Hrushevskyi there scientist discusses purely scientific problems. The scientist informs O.Broch about the activities of the Ukrainian Sociological Institute, asks to borrow the books he needed for work, consults on the possibilities of distributing emigration publications in Soviet Ukraine through the Nansen Mission, and gratefully sends him his and his daughter’s works. The published letters allow us to claim that it was M.Hrushevskyi who initiated the election of O.Broch as a valid member of the All-Ukrainian Academy of Sciences in June 1924. The last letters contain a discussion of the problem of establishing cooperation between O.Broch and the Ukrainian Academy of Sciences.